Multi-Environment Screening of Nepalese Finger Millet Landraces against Blast Disease [Pyricularia grisea (Cooke) Sacc.)] - Ghimire, Krishna Hari; Manandhar, Hira Kaji; Pandey, Madhav Prasad; Joshi, Bal Krishna; Ghimire, Surya Kanta; Karkee, Ajaya; Gurung, Suk Bahadur; Ghimire, Netra Hari; Gauchan, Devendra (Journal of Nepal Agricultural Research Council, 2022)
Three hundred finger millet genotypes (295 landraces from 54 districts and five released varieties) were evaluated for leaf, finger, and neck blast resistance under natural epiphytotic conditions across three hill locations in Nepal, namely Kabre, Dolakha (1740m); Vijaynagar, Jumla (2350 m); and Khumaltar, Lalitpur (1360 m) during the summer seasons of 2017 and 2018. The highest incidence of leaf, neck, and finger blast was observed at Lalitpur, followed by Dolakha and Jumla, whereas the overall disease incidence was higher in 2018 compared to 2017. Combined analysis over environments revealed non-significant differences among accessions for leaf blast, but the difference was highly significant for neck and finger blast. Correlation analysis suggested that there was a strong positive correlation between neck blast and finger blast (r = 0.71), leaf blast (seedling stage) and neck blast (r = 0.68), and leaf blast (seedling stage) and finger blast (r = 0.58) diseases. Among 300 accessions, 95 had lower scores for finger blast, 30 for neck blast, and 74 for leaf blast than the score of Kabre Kodo-2, the latest released variety in Nepal. Genotypes NGRC04798, NGRC03478, NGRC05765, NGRC03539, NGRC06484, NGRC01458, NGRC01495 and NGRC01597 were found the resistant genotypes for finger blast (2.1-2.3) and neck blast (1.5-2.3) based on pooled mean scores. This study shows the variable reactions of finger millet genotypes against blast disease in various environments and reports the promising landraces having field resistance to leaf, finger, and neck blast, which ultimately serve as important donors for blast resistance in finger millet breeding.